Algunas notas sobre periodismo científico y saber arqueológico - Carmona Jiménez, Javiera (Re-presentaciones: Periodismo, comunicación y sociedad, 2006)
This article begins with a general discussion of the difficulties pertaining to scientists, media, public and journalists, of disclosing science in Chile. It then discusses the specific characteristics of the relationship between scientific journalism and archaeology. The political, social and economic effects of science are a societal concern that extends beyond the field of scientific journalism, making them key issues of the social agenda. As such it is necessary to reinstate the social sciences to the repertoire of disciplines that are of interest to field of scientific journalism. Finally, we propose to consolidate the field of public communication of science and technology, as an object of investigation in order to understand what occurs to those involved in these processes, as well as the consequences of the irruption of the ciber journalism and the democratization of information promised by Internet, thus creating a “Citizen's Journalism" or participatory journalism.
Keywords: scientific journalism; spreading; Chilean archaeology; public communication of science and technology; ciber journalism; citizen journalism